2010
DOI: 10.1007/s00586-010-1650-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lumbar artificial disc design on intervertebral mobility: in vivo comparison between mobile-core and fixed-core

Abstract: Although in theory, the differences in design between fixed-core and mobile-core prostheses should influence motion restoration, in vivo kinematic differences linked with prosthesis design remained unclear. The aim of this study was to investigate the rationale that the mobilecore design seems more likely to restore physiological motion since the translation of the core could help to mimic the kinematic effects of the natural nucleus. In vivo intervertebral motion characteristics of levels implanted with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…On the other hand, a PEL angle greater than 5 • leads to the disappearance of the extension curve. This influence of the PEL angle on segmental mobility stems from the kinematics of the mobile-core implant [22]. The more posterior the mean center of rotation, the greater the (residual) segmental lordosis in maximum flexion.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, a PEL angle greater than 5 • leads to the disappearance of the extension curve. This influence of the PEL angle on segmental mobility stems from the kinematics of the mobile-core implant [22]. The more posterior the mean center of rotation, the greater the (residual) segmental lordosis in maximum flexion.…”
Section: Discussionmentioning
confidence: 98%
“…Par contre, un angle de LIP > 5 • entraîne une disparition de l'arc en extension. Cette influence de l'angle de LIP sur la MOB renvoie à la cinématique des prothèses à noyau mobile [22]. Plus le centre moyen de rotation est postérieur plus la lordose segmentaire (résiduelle) en flexion maximale est importante.…”
Section: Discussionunclassified
“…Previous studies have reported that 70-80% of adults suffer from low back pain-related diseases, thus making LIDD an important health issue (2,3). In the United States, 1-2% of the population has been reported to suffer from obvious intervertebral disc protrusion, whereas ~200,000 new cases are reported each year (3,4). Annular disruption, herniation of the nucleus pulposus, and oppression of the nerve root and cauda equina syndromeare among the main manifestations of LIDD (3).…”
Section: Introductionmentioning
confidence: 99%
“…Annular disruption, herniation of the nucleus pulposus, and oppression of the nerve root and cauda equina syndromeare among the main manifestations of LIDD (3). Although an early age of onset for low back pain is not uncommon, with symptoms sometimes appearing in patients as young as 20 years old, usually symptoms appear later in life, in patients between 30 and 40 years of age (4).…”
Section: Introductionmentioning
confidence: 99%